1996
DOI: 10.1042/bj3160787
|View full text |Cite
|
Sign up to set email alerts
|

Oligomannosides or oligosaccharide-lipids as potential substrates for rat liver cytosolic α-d-mannosidase

Abstract: We have previously reported the substrate specificity of the cytosolic alpha-D-mannosidase purified from rat liver using Man9GlcNAc, i.e. Man alpha 1-2Man alpha 1-3(Man alpha 1-2Man alpha 1-6)Man alpha 1-6(Man alpha 1-2Man alpha 1-2Man alpha 1-3) Man beta 1-4G1cNAc, as substrate [Grard, Saint-Pol, Haeuw, Alonso, Wieruszeski, Strecker and Michalski (1994) Eur. J. Biochem. 223, 99-106]. Man9 G1cNAc is hydrolysed giving Man5GlcNAc, i.e. Man alpha 1-2 Man alpha 1-2Man alpha 1-3(Man alpha 1-6)Man beta 1-4GlcNAc, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…None of these protein family members have any classical signal sequence or membrane-spanning domains, suggesting that they may not transit through the secretory pathway. Analysis of the known Ams1 homolog from rat suggested that it is localized to the ER and the cytosol (43,44); however, to our knowledge, the possibility of a lysosomal localization for this protein has not been fully explored. Ams1 and its homologs were recently categorized as the most ancestral ␣-mannosidase family in a global comparison within the ␣-mannosidase superfamily (45).…”
Section: Ams1 Utilizes the Autophagy Pathway For Vacuolar Delivery Unmentioning
confidence: 99%
“…None of these protein family members have any classical signal sequence or membrane-spanning domains, suggesting that they may not transit through the secretory pathway. Analysis of the known Ams1 homolog from rat suggested that it is localized to the ER and the cytosol (43,44); however, to our knowledge, the possibility of a lysosomal localization for this protein has not been fully explored. Ams1 and its homologs were recently categorized as the most ancestral ␣-mannosidase family in a global comparison within the ␣-mannosidase superfamily (45).…”
Section: Ams1 Utilizes the Autophagy Pathway For Vacuolar Delivery Unmentioning
confidence: 99%
“…A third route for oligosaccharide production (III) was hypothesized to be the result of the action of an endo-␤-N-acetylglucosaminidase (ENGase) acting upon N-linked glycoproteins to give rise to OS-Gn 1 (55). More recently, a fourth reaction (IV) involving formation of OS-Gn 2 from glycoproteins by the action of a PNGase, which cleaves the amide bond between the glycosylated Asn residue and the innermost GlcNAc residue, has been proposed (56,57). Indeed, the occurrence of both ENGase and PNGase in an ER-enriched fraction has been reported (58 -60).…”
Section: Minireview: Two-way Traffic Across the Er Membrane 10084mentioning
confidence: 99%
“…These enzymes are activated by cobalt, are relatively resistant to swainsonine, and can convert Man 5 GlcNAc to Man 3 GlcNAc. However, they act efficiently only on glycans with a single GlcNAc residue on their reducing end and appear to function in N-glycan catabolism rather than processing (33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%